(untitled) (Scientific Journal of Educational Management, Research and law, 2025)
The current study examined the relevance of lecturers in the Age of Artificial Intelligence: An exploratory study among selected universities in Rivers State. This study adopted a correlational research design in studying three (3) selected universities which constitutes accessible population. From the field survey, two hundred and fifty nine (259) copies of questionnaire were retrieved and analyzed; descriptive statistics was employed in analyzing the demographic data of respondents; also, Spearman’s Rank Order Correlations Coefficient from SPSS version 20.00 was the statistical tool utilized to examine the relationship between the dimensions of Artificial Intelligence and relevance of lecturers in the age Artificial Intelligence and the P-values obtained were used to test hypotheses postulated for the research between the variables. Findings revealed that Artificial Intelligence through its indicators of adaptive learning, automated grading and emotional artificial intelligence had weak relationship with the future relevance of lecturers in the teaching profession. However, it was concluded that human instructors are irreplaceable because they have special abilities including critical thinking, creativity and emotions, despite some participants’ beliefs that Artificial Intelligence would someday replace teachers and it was recommended the provision of educational training environments that add to improving the part of Artificial Intelligence applications in the professional development of lecturers to sustain their relevance in the profession.